Anatomy of antidepressant effect of light: the role of the BNST lesions - Avlar, Billur. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in the Social Sciences, 2008., 2008)
The aim of the present study was to shed light on the anatomy of antidepressant effect of bright light therapy. In line with this, lesions of the Bed Nucleus of the Stria Terminalis (BNST) which is implicated as an important relay area in mediating stress related circuitry in the brain, or sham operations were done in male Wistar rats. Nine weeks later, a single 10 min, 200 watt, 1350 lux bright light stimulus was administered at ZT21 (04:00) to lesioned (LL) or sham operated rats (SL). Control group animals; either lesioned (LC) or sham operated (SC) did not receive light stimulus. Behavioral despair was assessed by consecutive forced swim tests. The results replicated the aggravation of the immobility behavior in LC group and demonstrated an ameliorative effect of the light even in the presence of the BNST lesion (LL). These findings suggest that the BNST lesions confined to mostly the medial division do not have an integral role in mediating the antidepressant effects of light.
Keywords: Phototherapy.